A Equação de Klein-Gordon no Espaço-Tempo de Robertson-Walker - Gomes, D.; Notte Cuello, E.A.; de Oliveira, E.C. (Trends in Computational and Applied Mathematics, 2000)
We obtain, using the generalized derivate operators, the second order Casimir invariant operator associated to the Fantappié-de Sitter group, isomorphic to the 5-dimensional pseudorotation group, which is the group of motions admitted by the massless Robertson-Walker cosmological spacetime.